(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: Enuresis is a common presentation and is associated with significant distress to both child and parents. To date, there are no hospital-based studies evaluating enuresis in Nepal. The main objective of the study was to determine the socio-demographic and clinical profile of children with enuresis. Methods: It is a cross-sectional observational study conducted among out patients visiting the Child and Adolescent Psychiatry Unit at Kanti Children’s Hospital, Kathmandu, Nepal, from February 2024 to July 2024. A total of 2219 cases were screened using the Child and Adolescent Symptom Inventory parent version and diagnosis was based on Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Results: Out of 2219 cases screened, 35 cases met the diagnostic criteria of enuresis. The clinic-based prevalence of enuresis was 1.6%. The mean age of diagnosis was 9.63 ± 2.7 years with male to female ratio of 2.1:1. A total of 24 (68.6%) cases were referred by doctors, 20 (57.1 %) cases visited for reasons other than for enuresis and 19 (54.3%) cases had a positive family history of enuresis. A total of 34 cases (97.1%) had primary enuresis and 30 (85.7%) cases were having monosymptomatic symptoms. Psychiatry co-morbidity was found in 15 (42.9 %) cases. Conclusion: Enuresis is twice more common in boys compared to girls. Psychiatric co-morbidities are very common in children with enuresis.